2002
DOI: 10.1063/1.1525053
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution and property changes in Nd60Al10Fe20Co10 bulk metallic glass during crystallization

Abstract: The structural evolution and property changes in Nd 60 Al 10 Fe 20 Co 10 bulk metallic glass ͑BMG͒ upon crystallization are investigated by the ultrasonic method, x-ray diffraction, density measurement, and differential scanning calorimetry. The elastic constants and Debye temperature of the BMG are obtained as a function of annealing temperature. Anomalous changes in ultrasonic velocities, elastic constants, and density are observed between 600-750 K, corresponding to the formation of metastable phases as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
36
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 15 publications
3
36
0
Order By: Relevance
“…The first precipitated crystalline phase during HP annealing can be well identified as hexagonal Nd as indicated in figure 1. This is in agreement with that of the BMG crystallized at ambient pressure [5]. At higher temperature, the intensities of the crystalline reflections change.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…The first precipitated crystalline phase during HP annealing can be well identified as hexagonal Nd as indicated in figure 1. This is in agreement with that of the BMG crystallized at ambient pressure [5]. At higher temperature, the intensities of the crystalline reflections change.…”
supporting
confidence: 90%
“…It is also found that the Nd-based BMG can actually be regarded as a type of clustered amorphous material [2,5]. The direct evidence is that the HRTEM image of as-cast BMG exhibits a large numbers of nano-scale ordered regions dispersed in the glassy matrix, and the volume fraction is as large as 50% [5]. Clustered BMG exhibits hard magnetism while a ribbon sample without clustered structure is magnetically soft [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystallization and phase separation processes of several bulk metallic glasses ͑BMGs͒ have been investigated recently by various techniques including differential scanning calorimetry ͑DSC͒, [1][2][3] x-ray diffraction ͑XRD͒, 1-3 electron microscopy, 1,3,4 and small-angle neutron scattering ͑SANS͒. 4 -6 The role of diffusion in the decomposition and/or nucleation and growth phenomena near the glass transition temperature, T g , has been characterized and models have been suggested.…”
Section: Introductionmentioning
confidence: 99%